A role for repressive complexes and H3K9 di-methylation in PRDM5-associated brittle cornea syndrome - Porter, Louise; Galli, Giorgio; Williamson, Sally; Selley, Julian; Knight, David; Elcioğlu, Nursel; Aydın, Ali; Elcioğlu, Mustafa; Venselaar, Hanka; Lund, Anders; Bonshek, Richard; Black, Graeme; et al. (Oxford University Press, 2015)
Type 2 brittle cornea syndrome (BCS2) is an inherited connective tissue disease with a devastating ocular phenotype caused by mutations in the transcription factor PR domain containing 5 (PRDM5) hypothesized to exert epigenetic effects through histone and DNA methylation. Here we investigate clinical samples, including skin fibroblasts and retinal tissue from BCS2 patients, to elucidate the epigenetic role of PRDM5 and mechanisms of its dysregulation in disease. First we report abnormal retinal vascular morphology in the eyes of two cousins with BCS2 (PRDM5. exons 9-14) using immunohistochemistry, and mine data from skin fibroblast expression microarrays from patients with PRDM5 mutations p.Arg590* and. exons 9-14, as well as from a PRDM5 ChIP-sequencing experiment. Gene ontology analysis of dysregulated PRDM5-target genes reveals enrichment for extracellular matrix (ECM) genes supporting vascular integrity and development. Q-PCR and ChIP-qPCR confirm upregulation of critical mediators of ECM stability in vascular structures (COL13A1, COL15A1, NTN1, CDH5) in patient fibroblasts. We identify H3K9 di-methylation (H3K9me2) at these PRDM5-target genes in fibroblasts, and demonstrate that the BCS2 mutation p.Arg83Cys diminishes interaction of PRDM5 with repressive complexes, including NuRD complex protein CHD4, and the repressive chromatin interactor HP1BP3, by co-immunoprecipitation combined with mass spectrometry. We observe reduced heterochromatin protein 1 binding protein 3 (HP1BP3) staining in the retinas of two cousins lacking exons 9-14 by immunohistochemistry, and dysregulated H3K9me2 in skin fibroblasts of three patients (p.Arg590*, p.Glu134* and Delta exons 9-14) by western blotting. These findings suggest that defective interaction of PRDM5 with repressive complexes, and dysregulation of H3K9me2, play a role in PRDM5-associated disease.
Keywords: Repressive; Complexes; Cornea Syndrome